To Study the Procession of Learner-Centered Approach in Teaching and Learning English Subject at Sayaboury Secondary School - MOUNGKHOUNSAVAT, Phoutthasay; VATHANAVONG, Thongthiane; PANFONGPHET, Sipaseuth; VATHANAVONG, Phaivanh; PHATTHANA, Bounyong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This paper focuses on the relevant information on initiatives to conduct student-centered approaches. The study aimed to explore the procession of teaching performance of the Learner-centered teaching and learning English subject at Sayaboury secondary school. The samples group 23 people that included administrators and English teachers. The study’s conceptual framework consisted of 5 aspects – 1. The preparation of the educational institution, 2. The development of teachers in the educational institution, 3. The promotion of learning style, 4. Media of teaching materials and 5. the evaluation of teaching and learning management. The research tool was the 5-rating-scale questionnaire for teachers and administrators. The completed program was applied for the interpretation of statistics in terms of Frequency, Percentage, Mean and Standard Deviation. The result revealed that the state of teaching performance of the learner-centered teaching and learning situation was at a high level. The opinions of administrators and English teachers are unanimous of all 5 aspects without a statistically significant interval at the 0.05 level.